Two functionally distinct domains generated by in vivo cleavage of Nup145p: a novel biogenesis pathway for nucleoporins - Teixeira, Maria Teresa; Siniossoglou, Symeon; Podtelejnikov, Sasha; Bénichou, Jean Claude; Mann, Mattias; Dujon, Bernard; Hurt, Ed; Fabre, Emmanuelle (The EMBO journal, 1997)
Nup145p is an essential yeast nucleoporin involved in nuclear export of polyadenylated RNAs. We demonstrate here that Nup145p is cleaved in vivo to yield two functionally distinct domains: a carboxy‐terminal domain (C‐Nup145p) which is located at the nuclear pore complex (NPC) and assembles into the Nup84p complex, and a GLFG‐containing amino‐terminal domain (N‐Nup145p) which is not part of this complex. Whereas the essential C‐Nup145p accomplishes the functions required for efficient mRNA export and normal NPC distribution, N‐Nup145p, which is homologous to the GLFG‐containing nucleoporins Nup100p and Nup116p, is not necessary for cell growth. However, the N‐Nup145p becomes essential in a nup188 mutant background. Strikingly, generation of a free N‐domain is a prerequisite for complementation of this peculiar synthetic lethal mutant. These data suggest that N‐ and C‐domains of Nup145p perform independent functions, and that the in vivo cleavage observed is of functional importance.
Gesehen am 01.12.2025